Dermoscopy the essentials - Soyer, H. Peter (Elsevier/Saunders, 2012)
Presents the practical guidance you need to master dermoscopy - an effective, cheaper, and less invasive alternative to biopsy. This title explains various aspects of performing dermoscopy and interpreting results.